MEK-1 phosphorylation by MEK kinase, Raf, and mitogen-activated protein kinase: analysis of phosphopeptides and regulation of activity. - Gardner, A M (1994)
MEK-1 is a dual threonine and tyrosine recognition kinase that phosphorylates and activates mitogen-activated protein kinase (MAPK). MEK-1 is in turn activated by phosphorylation. Raf and MAPK/extracellular signal-regulated kinase kinase (MEKK) independently phosphorylate and activate MEK-1. Recombinant MEK-1 is also capable of autoactivation. Purified recombinant wild type MEK-1 and a mutant kinase inactive MEK-1 were used as substrates for MEKK, Raf, and autophosphorylation. MEK-1 phosphorylation catalyzed by Raf, MEKK, or autophosphorylation resulted in activation of MEK-1 kinase activity measured by phosphorylation of a mutant kinase inactive MAPK. Phosphoamino acid analysis and peptide mapping identified similar MEK-1 tryptic phosphopeptides after phosphorylation by MEK kinase, Raf, or MEK-1 autophosphorylation. MEK-1 is phosphorylated by MAPK at sites different from that for Raf and MEKK. Phosphorylation of MEK-1 by MAPK does not affect MEK-1 kinase activity. Several phosphorylation sites present in MEK-1 immunoprecipitated from 32P-labeled cells after stimulation with epidermal growth factor were common to the in vitro phosphorylated enzyme. The major site of MAPK phosphorylation in MEK-1 is threonine 292. Mutation of threonine 292 to alanine eliminates 90% of MAPK catalyzed phosphorylation of MEK-1 but does not influence MEK-1 activity. The results demonstrate that MEKK and Raf regulate MEK-1 activity by phosphorylation of common residues and thus, two independent protein kinases converge at MEK-1 to regulate the activity of MAPK.